Does an increase in education quality cause developing countries to catch up? - Łukasz Goczek; Bartosz Witkowski; Ewa Witkowska (International Journal of Management and Economics, 2022)
We investigate whether increasing the education quality causes increases in economic growth allowing poorer countries to catch up. To this end, we extend Nelson-Phelps's classic paper by introducing differences in education quality (proxied by students' performance on the Program for International Student Assessment [PISA] test) in a leader-follower type of growth model with knowledge diffusion. We use students' performance in a standardized international PISA test to measure education quality's impact on economic growth using a panel Vector Error Correction allowing for cross-correlation in the co-integration analysis in a set of all countries observed over the years 1975-2018. Additionally, we consider the possible reverse causality that characterizes economic development and the quality of education. Our results confirm the relevance of education quality as a significant causal factor of economic growth. However, further analyses indicate that the discussed relation is long-run, which may have important implications for policymakers.
Keywords: C4; C5; I2; O1; 650; economic growth; economics of education; educational policy; international education/studies